The Development of Short Story Creative Writing Teaching Materials in Wetland Environment - Ahsani Taqwiem; Lita Luthfiyanti (Scholars Journal of Arts, Humanities and Social Sciences, 2023)
This research objective was to design teaching materials containing short story writing material for students taking Creative Writing Courses. Writing short stories is a complex competency, even for undergraduate students. Various problems arise in the creative writing process. One is the lack of learning materials that suit the students’ needs. Therefore, this research aimed at developing materials to solve the lack of teaching materials related to writing short stories. The object of this research and development consisted of students who took creative writing courses at the Indonesian Language and Literature Education study program, Faculty of Teacher Training and Education, Lambung Mangkurat University. This research procedure included (1) conducting needs analysis, (2) developing teaching materials, (3) designing and conducting formative evaluations, (4) revising teaching materials, and (5) conducting summative evaluations or product trials. The material that has been completed has gone through a trial phase for students and showed an increase in students’ knowledge and skills in writing short stories